Negotiations on a Ceasefire in the Process of Resolving an International Conflict: Theory and Practice - Sergii Tolstov (Ukrainian Policymaker)
International assistance in ceasefire negotiations is an important and necessary phase preceding the political settlement of an international conflict. At the same time, as the experience of the conflict on the Korean Peninsula shows, achieving a truce does not yet guarantee a settlement of the conflict. In the form of political confrontation between the parties, the conflict may continue for further decades. However, the very fact of ending the active phase of confrontation at the battlefield undoubtedly has a positive impact on the state of international relations and creates the prospect of peaceful development for the subsequent countries and their peoples.In the case of a ceasefire the development of events within the post-conflict phase depends both on the goals and intentions of the direct participants involved in the conflict and on the participation and influence of external actors. Of course, constructive efforts by external actors can significantly contribute to the resolution of the contradictions that led to the war. However, given the experience of the RussianUkrainian war ongoing since February 2022 it seems appropriate to separate the phase of cessation of hostilities in the sense of achieving a sustainable truce and the phase of political settlement. From the author’s viewpoint at the stage of promoting an armistice different mediation efforts of the states whose governments are interested in ending the Russian-Ukrainian war may prove more effective than in the context of the search of solutions that eliminate initial causes that led to the military confrontation between the parties to the conflict. In this context, creating conditions for ending the active phase of military actions seems to be an important and urgent task ensuring the end of a dangerous military crisis that has destroyed the foundations of European security.